Investigating the Reliability of Empirical Path Loss Models over Digital Terrestrial UHF Channels in Ikorodu and Akure, Southwestern Nigeria - Akinsanmi Akinbolati; Bolanle T. Abe (Telecom)
It is well known that existing empirical models cannot fit perfectly into environments other than those they were formulated in due to differences in terrain and climate. The Okumura–Hata family of models are gaining acceptability over the VHF/UHF channels. However, it is imperative to investigate their reliability and to use the one most suited to each environment. This study investigated the reliability of the Okumura–Hata, COST-231, ECC-33, and Ericsson models over digital UHF channels in Ikorodu and Akure, Southwestern Nigeria. The drive test protocol was used for data collection at intervals of 1 km along different routes from the experimental stations up to maximums of 10 and 16 km in Ikorodu and Akure, respectively. This was carried out for both wet and dry season months using a digital Satlink meter with a spectrum (WS-6936), GPS Map 78s and a field vehicle. The uniqueness of this study is that it used real-world data with a seasonal scope, and the mean values were employed in the analysis to strengthen the reliability of the results. The measured path loss (MPL) and predicted path loss (PPLM) were computed, with error margin analysis carried out between them. The results reveal a mean MPL of 110.42 dB in Ikorodu, while the PPLMs were 121.90, 123.55, 158.42, and 291.01 dB for the Hata, COST-231, Ericsson, and ECC-33 models, respectively. In Akure, the mean MPL was 123.157 dB, while the PPLMs were 121.922, 130.179, 198.979, and 313.494 dB. The results further indicate that the Hata model had the best performance with the lowest RMSE of 10.812 in Ikorodu, while COST-231 had the best performance in Akure, with the lowest RMSE of 9.877. The optimized Hata and COST-231 models were developed with improved RMSEs of 5.895 and 7.815 for the Ikorodu and Akure environments, respectively. The optimized models had higher degrees of reliability and will provide a valuable approach to wireless communication planning in tropical urban and suburban environments for achieving quality of transmission and reception (QoTnR) over UHF channels in Nigeria and similar environments in Africa.